(Why) Do Self-Employed Parents Have More Children? - Nzinga Broussard; Ralph Chami; Gregory Hess (Center for Economic Studies and ifo Institute (CESifo), 2003)
We provide a theory whereby non-benevolent, self-employed households increase their expected family size to raise the likelihood that an inside family member will be a good match at running the business. Hence, having larger family sizes raises the self-employed household's expected return to their business. Using data from the General Social Survey, we find that respondents have approximately .2 to .4 more actual and expected number of children if they are self-employed as compared to if they are not self-employed. This empirical relationship is established across a broad array of sub-samples using a simple differences in means test. As well, the empirical relationship holds using a regression framework, including the use of instrumental variables estimation to allow for the possibility of endogeneity of the respondent's self-employment status and whether the respondent's spouse stays at home.
Keywords: 330; self-employed; children; familiy business; matching